De Coco Shake - Fahmi, Muhammad Khairul; Yusop, Yusliana; Masri, Ramona; Tagandap, Alexander; Jami, Siti Nurajjar (2012)
De Coco Shake is a partnership business that its involvement is from five young people with creative thinking and great ideas in business. These five people are academically qualified and trained to be successful entrepreneur one fine day. It is align with the government vision to increase the members of Bumiputera entrepreneurs. Thus, it is the partners" obligation and responsibilities to make it possible and achievable. De Coco Shake will start its operations on December, 1 2013. The partners will make contribution with total of RM 49,370.00. The location of business will be at Tanjung Aru First Beach, Tanjung Aru, Kota Kinabalu, Sabah. Our business is a food premise that prepares and sells coconut shake with chocolate rice in additional of ice-cream. Most Malaysian, enjoy drinking coconut water especially in hot day by the beach. Thus, in our business, we do an innovation on the available coconut water and coconut shake where we upgraded it to secret recipe coconut shake with chocolate rice. In this perspective we can see where traditional and modern ascents met. As such the need for drink that gives satisfaction will always be there, so we provide it with reasonable price that affordable by everyone.